2016
DOI: 10.1353/cpr.2016.0069
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of an Innovative Community-Engaged Health Navigator Program to Address Social Determinants of Health

Abstract: One of the important innovations of the pathways approach is a shift in focus from merely providing discrete services to confirming healthy outcomes for the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Our interpretation is that this sharing and empathy likely contribute to the lower and more sustained levels of depression symptoms. Participants at both sites indicated the importance of these factors in qualitative data, and our broader research with Latina and Mexican immigrant women and CHWs in Albuquerque strongly supports this finding of the deep importance of social support in the lives of Latinxs[90][91][92][93][94][95]. In fact, this is why our patient advisors were adamant that we find a way to include social support and social context in the design of our study, and why we enrolled participants as patient participant-social support participant dyads rather than merely recruiting patient participants to participate as individuals.Furthermore, although patient participants at both sites rated their program high in cultural competence and expressed that they really like the program and the staff, when posed with a question about what was missing from the program design, DSMS patient participants tended to indicate that the DSMS model of six discrete group sessions was not really sufficient and was less attractive than a program like the CCM that provides ongoing classes and support.DSMS patient participants and their social support participants reported that patient participants often feel socially isolated and alone in relation to the issue of diabetes-and CCM patient participants discussed the importance of having the social support of the program in an ongoing way.…”
supporting
confidence: 62%
“…Our interpretation is that this sharing and empathy likely contribute to the lower and more sustained levels of depression symptoms. Participants at both sites indicated the importance of these factors in qualitative data, and our broader research with Latina and Mexican immigrant women and CHWs in Albuquerque strongly supports this finding of the deep importance of social support in the lives of Latinxs[90][91][92][93][94][95]. In fact, this is why our patient advisors were adamant that we find a way to include social support and social context in the design of our study, and why we enrolled participants as patient participant-social support participant dyads rather than merely recruiting patient participants to participate as individuals.Furthermore, although patient participants at both sites rated their program high in cultural competence and expressed that they really like the program and the staff, when posed with a question about what was missing from the program design, DSMS patient participants tended to indicate that the DSMS model of six discrete group sessions was not really sufficient and was less attractive than a program like the CCM that provides ongoing classes and support.DSMS patient participants and their social support participants reported that patient participants often feel socially isolated and alone in relation to the issue of diabetes-and CCM patient participants discussed the importance of having the social support of the program in an ongoing way.…”
supporting
confidence: 62%
“…In 2014, the Institute of Medicine recommended that health care settings begin to screen for and report on HRSN (Institute of Medicine, 2014). To act upon this recommendation, many primary care practices have implemented screening processes (Andermann, 2018; Fraze et al., 2019; Page‐Reeves et al., 2016; Smith et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the Institute of Medicine recommended that health care settings begin to screen for and report on social determinants of health (SDOH)related needs, 1 leading to development of screening tools and increasing implementation of screening processes. [2][3][4][5] However, even earlier, the American Academy of Pediatrics and others recommended screening for food insecurity (FI) in health care settings. 6,7 FI is defined by the U.S. Department of Agriculture as "a household level economic and social condition of limited or uncertain access to adequate food."…”
Section: Introductionmentioning
confidence: 99%